Letter from Carl D. Duncan to Patricia Whiting, February 4, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Whiting refers to Duncan as Godfather in a Valentine. Duncan reassures Whiting that he is not bothered that she canceled plans with him to go camping with friends and expresses his admiration for her throughout.